Quantitative insights into outcome-based education: a bibliometric exploration - Jeena Joseph; Jobin Jose; Anat Suman Jose; Gilu G. Ettaniyil; Joby Cyriac; Shaiju K. Sebastian; Ajesh P. Joseph (International Journal of Evaluation and Research in Education (IJERE), 2024)
Outcome-based education (OBE) is a method of educational approach that focuses on defining specific learning outcomes or objectives that students should achieve by the end of a course, program, or educational experience Instead of merely following a predetermined curriculum, OBE places focus on what learners should be able to accomplish or display as a result of their learning. A thorough bibliometric analysis utilizing biblioshiny and VOSviewer is used in this work to dive into the world of outcome-based education. This investigation attempts to offer quantitative insights into the development, trends, and significant contributors in the area of OBE by carefully examining a wide range of academic articles. The study encompasses a broad temporal range, capturing developments in the field from its inception in 1978 to 2023, thereby offering a comprehensive overview of its evolution over time. Patterns in research production, significant works, prolific authors, and collaboration networks appear via the prism of bibliometric approaches, illuminating the complex OBE landscape. This study not only contributes to the understanding of OBE’s scholarly landscape but also underscores the significance of bibliometric approaches in illuminating trends and shaping future research directions.